2022
DOI: 10.1177/03611981221086918
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of a Tack Coat Bond Strength Test to Minimize the Potential for Slippage Failures on Flexible Airfield Pavements

Abstract: Slippage failures on flexible pavements are a potential problem for airports given the large wheel loads and high tire pressures of modern aircraft. While not common, when slippage failures do occur the impact can be significant on flexible pavement performance. This paper has three components: (1) case studies of slippage failures that have occurred on airfield pavements; (2) a literature review of relevant interlayer bond strength test procedures; and (3) the results of an analytical, field, and laboratory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Overall, with the exception of wet RAP at 7 percent binder content, the ITS results ranged from 149 to 226 psi. Other research groups reported a range of ITS for DGA at room temperature of approximately 150 to 200 psi, which is similar to the data presented in Figure 3 [13,14]. The ITS of a cold patch product averaged approximately 10 psi, which is much lower than the RAP-EPB mixture [1].…”
Section: Resultssupporting
confidence: 81%
“…Overall, with the exception of wet RAP at 7 percent binder content, the ITS results ranged from 149 to 226 psi. Other research groups reported a range of ITS for DGA at room temperature of approximately 150 to 200 psi, which is similar to the data presented in Figure 3 [13,14]. The ITS of a cold patch product averaged approximately 10 psi, which is much lower than the RAP-EPB mixture [1].…”
Section: Resultssupporting
confidence: 81%